U.S. Re‐Licensure Opioid/Pain Management Continuing Education Requirements in Dentistry, Dental Hygiene, and Medicine. Issue 10 (1st October 2019) - Wiener, R. Constance; Waters, Christopher; Bhandari, Ruchi; Trickett Shockey, Alcinda K.; Panagakos, Fotinos
Abstract : Drug‐induced deaths have been accelerating over the last two decades. The aim of this study was to determine if states with high opioid‐induced deaths and overall drug‐induced deaths were more likely to have continuing education (CE) requirements related to opioid use/pain management than states with fewer opioid‐induced deaths. Almost 200 state dental and medical law boards' websites were examined for CE requirements, license renewal periods, and CE requirements for opioid use/pain management in December 2018 and January 2019. Drug‐induced death data were obtained from the Centers for Disease Control and Prevention online database. States were categorized into quartiles of opioid‐induced deaths per 100, 000 population. A similar categorization was created for all drug‐induced deaths. The results showed that states in the second, third, and fourth quartiles of opioid‐induced deaths were more likely to have dental boards requiring opioid use/pain management CE than states in the first quartile in dentistry. This pattern was not the case with the medical boards' requirements. Dentists and physicians in states with higher all drug‐induced deaths per 100, 000 population were as likely to be required to attend opioid use/pain management CE as dentists and physicians in states with lower opioid‐induced deaths. Although many licensing boards require opioid use/pain management CE in relation to their opioid‐induced death rates, there is a need for policies to increase education in substance use disorders to reduce the number of drug‐induced deaths.